2011
DOI: 10.1007/s12011-011-8995-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Selenium Affects Selenoprotein W Gene Expression in the Liver of Chicken

Abstract: As selenium in the form of "Selenoprotein W (SelW)" is essential for the maintenance of normal liver function, the expression of SelW liver depends on the level of selenium supplied with the diet. Whereas this is well known to be the case in mammals, relatively little is known about the effect of dietary Se on the expression SelW in the livers of avian species. To investigate the effects of dietary Se levels on the SelW mRNA expression in the liver of bird, 1-day-old male chickens were fed either a commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…The data indicated that Se contents in gastrointestinal tract tissues correlated with ingested Se levels. These results confirm previous studies showing that Se affects the expression of SelW [23,32,33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data indicated that Se contents in gastrointestinal tract tissues correlated with ingested Se levels. These results confirm previous studies showing that Se affects the expression of SelW [23,32,33].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in our lab have shown that the cDNA for chicken SelW can be cloned from Se-supplemented chicken cerebral tissue; we also found that SelW is ubiquitously expressed in diverse tissues of chicken [19,41]. The SelW mRNA distribution in the liver, pancreas, gastrointestinal tissues, and immune organs with different dietary selenium levels have yet to be determined [23,32,33,42]. In the present study, the results of feeding two levels of dietary Se (0.15 and 1.5 mg) for 55 days indicated that SelW gene expression in the chicken gastrointestinal tract was sensitive to dietary Se concentrations and was consistent with these earlier studies.…”
Section: Discussionmentioning
confidence: 74%
“…Se implements its biological function through incorporation into selenoproteins. In addition, Se deficiency caused injuries in several different chicken organs, including the brain (Sheng et al 2014;Xu et al 2013), muscles (Yao et al 2013a, b), the gastrointestinal tract (Gao et al 2012), the spleen (Yu et al 2011) and the liver (Sun et al 2011). The study of Fischer showed that the liver contains a high concentration of Se, which participates in many biological processes that range from cellular antioxidant defense to the protection and repair of DNA to apoptosis (Fischer et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…SelW expresses ubiquitously in diverse tissues of chicken and particularly high in skeletal muscle tissues [10,33]. Its mRNA distributions in liver, pancreas, gastrointestinal tissues (tongue, esophagus, corp, proventriculus, gizzard, duodenum, small intestine, cecum, and rectum), and immune organs (thymus, bursa of Fabricius, and spleen) with different dietary selenium levels have been determined [21][22][23]34]. Chickens fed the diets containing 1-3 mg/kg sodium selenite have significant increases of SelW mRNA level in the gastrointestinal tract tissues but decreases in the esophagus, crop, proventriculus, gizzard, duodenum, and cecum in chickens fed the diet containing 5 mg/kg sodium selenite [22].…”
Section: Discussionmentioning
confidence: 99%